The Influence of Religious Literacy on Students' Social Behavior in Srengseng Primary School, Jakarta - Fadlan, Muhammad; Hayun, Muhammad (IJBLE Scientific Publications Community Inc., 2024)
The background to writing this thesis is that religious literacy regarding the social behavior of class V students at SD Negeri Srengseng 01 and SD Negeri Srengseng 04 is still relatively low and deviant behavior still occurs, so researchers are interested in researching what causes this. Researchers propose solutions for implementing religious literacy in schools. This research aims to determine the influence of religious literacy on students' social behavior. The method used by researchers in this research is a quantitative method with a survey approach with the hypothesis that there is an influence of religious literacy on students' social behavior. The results of this research show that there is an influence of religious literacy on the social behavior of students at Srengseng 01 and 04 public elementary schools. This is proven by the calculation results showing the F test calculation result is 95.157, thus it can be concluded that there is an influence and a large influence of religious literacy on students' social behavior. It is hoped that the results of this research will be useful for related parties such as school principals, teachers, parents, students and future researchers